Characteristics of Risky Internet Behavior and Psychological Intervention Methods among College Students in Reproductive Health Management - Xie, Li; Wang, Shaoqing; Jiang, Xiaoyan (Pacific International Journal, 2024)
In recent years, the phenomenon of internet dependency among college students in reproductive health management has become increasingly severe, particularly with the widespread adoption of online education, which has significantly increased the time they spend online, exacerbating internet dependency issues. Internet dependency not only affects academic performance and daily life but can also lead to psychological and social problems such as anxiety, depression, and social withdrawal. Therefore, early detection of risky internet behavior in students has become an important topic. This paper summarizes the characteristics of risky internet behavior among college students through literature research, including loss of time management, noticeable emotional fluctuations, changes in social behavior, and decline in academic performance. It proposes a series of measures for the early identification and intervention of risky internet behavior, providing references for educators and parents. The results of this study show that early detection of risky internet behavior in college students and active psychological intervention are of great significance.